Epistemological Misunderstandings and Polycentric Resistance: Dutch Colonial Interaction with the Minangkabau Society in the Early Padri Conflict (West Sumatra, 1819–1825) - Andoni, Yudhi; Yulia, Novi (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2025)
In the early 19th century, Dutch colonial misinterpretations of Minangkabau society were not passive deficiencies but active instruments of resistance. Local communities strategically transformed colonial ignorance into autonomous spaces. This thesis reframes colonial narratives by highlighting polycentric agency—from coffee-hiding farmers to salt-innovating clerics—which systematically exploited Dutch epistemological blind spots. Thus, colonial failure was structural-epistemological, not merely technical-military; territorial occupation did not equate to political control. Consequently, the colonized Minangkabau society’s resilience oftenthe resilience of the colonized Minangkabau society often resided in its capacity to convert the colonizer’s weakness (ignorance) into a source of counter-hegemonic strength